AMYLOIDOSIS - Rahşan Kamiloğlu; Yeşim Kurtaiş Gürsel (Archives of Rheumatology, 2003)
Amyloidosis is a disease presenting with accumulation of protein-like materials that are not soluble in extracellular fluid of tissues. This accumulation can be localized to a single organ or it can be systemic. Amyloidosis is usually subclinical, but many different manifestations may also be observed. Sometimes the disease resembles the clinical characteristics of rheumatologic diseases. Amyloidosis may also appear as a result of long lasting inflammatory conditions including rheumatological diseases. There are no specsific treatment modalities eliminating the amyloid deposits, but therapies that reduce the amyloid fibril precursor proteins and support the functions of organs that are involved can improve survival and preserve function.